Morphological description and DNA barcoding of Hydrobaenus laticaudus Sæther, 1976 (Diptera: Chironomidae: Orthocladiinae) from Amur River basin (Russian Far East) - Makarchenko, Eugenyi A.; Makarchenko, Marina A.; Semenchenko, Alexander A. (Zootaxa, 2019)
Illustrated redescription of adult male and description for the first time of pupa and fourth instar larva, as well as DNA barcoding, of Hydrobaenus laticaudus Sæther in comparison with close related known species of Hydrobaenus Fries, and an updated part of a key to species of Hydrobaenus from the Russian Far East are provided. A reference 658 bp barcode sequence from a fragment of the mitochondrial gene cytochrome oxidase I (COI) was used as a tool for species delimitation. For the estimation of interspecific distances and constructing detailed Bayesian tree within Hydrobaenus, we have obtained DNA barcoding for the two other species, H. distinctus and Hydrobaenus sp.1. The intraspecific sequence divergence of H. laticaudus based on the Kimura-2-parameter (K2P) distance ranged from 0.0–0.031, whereas the interspecific sequence divergence based on the K2P distance ranged from 0.106-0.197% between H. laticaudus and other species of genus Hydrobaenus. The well-supported monophyly as well as results of an ABGD analysis confirms the validity of H. laticaudus.